Exome sequencing identifies mutations in LZTFL1, a BBSome and smoothened trafficking regulator, in a family with Bardet–Biedl syndrome with situs inversus and insertional polydactyly. Issue 5 (17th April 2012) - Marion, Vincent; Stutzmann, Fanny; Gérard, Marion; De Melo, Charlie; Schaefer, Elise; Claussmann, Aurélie; Hellé, Sophie; Delague, Valérie; Souied, Eric; Barrey, Catherine; Verloes, Alain; Stoetzel, Corinne; et al.
Abstract : Background: Bardet–Biedl Syndrome (BBS) is an emblematic recessive genetically highly heterogeneous ciliopathy characterised mainly by polydactyly, retinitis pigmentosa, obesity, cognitive impairment, and kidney dysfunction. The 16 BBS genes known to date are implied in the primary cilia related cellular pathways. Methods and results: Single nucleotide polymorphism (SNP) array analysis followed by exome sequencing was performed in a consanguineous family diagnosed with BBS with unusual developmental features, namely situs inversus and insertional polydactyly. A homozygous 5 bp deletion (NM_020347.2:c.402-406del, p.Pro136ThrfsX5) in LZTFL1 was identified. No LZTFL1 transcript was found in the patient's fibroblasts and no protein could be detected. The sonic hedgehog (Shh) pathway analysis conducted on the patient's fibroblast showed a significant increase in Smo. Patched1 as well as the downstream target GLI2 were also found to be upregulated, indicating an overall massive activation of the Shh signalling in the absence of LZTFL1. Conclusion: LZTFL1, encoding the human leucine zipper transcription factor like 1, has been recently shown to be an important negative regulator of BBSome ciliary trafficking and Shh signalling. This study shows that absence of LZTFL1 leads to a BBS phenotype with enhanced developmental abnormalities associated with cellular Shh dysfunction. LZTFL1 is a novel BBS gene ( BBS17 ).